2017
DOI: 10.1038/ncomms14516
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the molecular organization of the translocon-associated protein complex

Abstract: In eukaryotic cells, one-third of all proteins must be transported across or inserted into the endoplasmic reticulum (ER) membrane by the ER protein translocon. The translocon-associated protein (TRAP) complex is an integral component of the translocon, assisting the Sec61 protein-conducting channel by regulating signal sequence and transmembrane helix insertion in a substrate-dependent manner. Here we use cryo-electron tomography (CET) to study the structure of the native translocon in evolutionarily divergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
219
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 145 publications
(227 citation statements)
references
References 43 publications
8
219
0
Order By: Relevance
“…Biochemical studies suggested that Ost1 and Wbp1 recognize acceptor and donor substrates, respectively 8,21,22 . The structures of the eukaryotic OST have been limited to low-resolution EM reconstructions, hindering a mechanistic understanding of protein N-glycosylation in eukaryotes 2326 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical studies suggested that Ost1 and Wbp1 recognize acceptor and donor substrates, respectively 8,21,22 . The structures of the eukaryotic OST have been limited to low-resolution EM reconstructions, hindering a mechanistic understanding of protein N-glycosylation in eukaryotes 2326 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent cryo-electron tomographic studies showed the relative positions of mammalian translocons and OSTs bound to the ribosomes 24,26 . However, the detailed interface—i.e., which subunits mediate the OST/translocon interaction—was unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These three-dimensional views revealed novel protein arrays within the Golgi cisternae [1], shed light on the structures of individual nuclear pore complexes [2], and visualized polyribosomes attached to the endoplasmic reticulum [3]. All of these macromolecular complexes were captured in their native environment using cryo-electron tomography (CET).…”
Section: Introductionmentioning
confidence: 99%
“…Cryo-FIB has enabled cryoelectron tomography (cryo-ET) of plunge-frozen hydrated cells, revealing the cellular interior with sufficient resolution and contrast to study membrane-bound macromolecules in their native state [4][5][6][7].…”
mentioning
confidence: 99%
“…Cryo-FIB has enabled cryoelectron tomography (cryo-ET) of plunge-frozen hydrated cells, revealing the cellular interior with sufficient resolution and contrast to study membrane-bound macromolecules in their native state [4][5][6][7].In the current standard cryo-FIB preparation technique, lamellas are milled on plunge-frozen TEM grids by completely removing material over tens of micrometers on both sides of the lamella, while the lamella itself remains connected to the bulk material on the grid. Several lamellas can be prepared on a single grid, which is then imaged directly by cryo-ET [8].…”
mentioning
confidence: 99%